The Implementation of Float Tray System Technology for Production of Tobacco - Romina Kabranova, K.Kochoska, R. Mavroski (https://dergipark.org.tr/en/pub/sduzfd/issue/40528, 2018)
Macedonia is characterized by a highly variable climate that has already experienced an increase in mean temperature and moisture deficits, as well as an increase in the severity of extreme events like drought, heat waves and forest fires. As for climate change, tobacco is one of the most stable crops in which the changes will not have such a drastic impact on further production, primarily because of the high adaptability of tobacco as a plant. To improve tobacco production is necessary good agricultural practice, which involves the implementation of new technologies for production of tobacco seedlings. The aim of study was to represent the current situation of tobacco production in Macedonia, and to give further directions using the advanced technology, in order to improve production, and facilitate the work of people whose existence depends on this crop. Research was conducted on oriental tobacco varieties: prilep NS 72 and yaka YV 125/3. This paper provides a primary information for obtaining high-quality tobacco seedlings, based on the benefits that ensure new Float Tray System technology.
1st International Agricultural Structures and Irrigation Congress Special Issue Publisher: Isparta Uygulamalı Bilimler Üniversitesi
Keywords: Float Tray System, tobacco production